Comparative Analysis of the Fatty Acid Pattern of Silybum marianum with Nigella sativa by Gas Chromatography-Mass Spectrometry - N. Sabir, Mohammed; K. Rachid, Shwan (Iraqi Journal of Pharmaceutical Sciences, 2017)
Many studied were conducted to evaluate the antihepatotoxic and antioxidant activities of Silybum marianum and proved these actions. The Naturally grown seed in Iraqi-Kurdistan Region also were studied for its chemical contents and biological activities. Vegetable oils occur in various plant parts mainly concentrated in the seeds. In this study comparison was made between the fatty acid patterns of two plant seeds, Silybum marianum and Nigella sativa. Seed sample of Silybum marianum and Nigella sativa were exposed for extraction and isolation of the fatty acid contents using two different solvents (petroleum ether and n-hexane) at 60-80oC using soxhlet apparatus and the oily extract were purified and analysed by GC-MS triplet system. Result showed that extraction with petroleum ether yielded 23% and 24% of total weight of the seeds of Silybum marianum and Nigella sativa respectively and comparable results with n-hexane extract yielded 17% and 22% of total seed weight of Silybum marianum and Nigella sativa respectively showing significant differences in the fatty acids patterns of both plants under research. Key words: Fatty acids, GC-MS, Silybum marianum, natural products, cardiovascular diseases.